Bordetella pertussis pertactin knock-out strains reveal immunomodulatory properties of this virulence factor - Hovingh, Elise Sofie (Emerg Microbes Infect, 2018)
Whooping cough, caused by Bordetella pertussis, has resurged and presents a global health burden worldwide. B. pertussis strains unable to produce the acellular pertussis vaccine component pertactin (Prn), have been emerging and in some countries represent up to 95% of recent clinical isolates. Knowledge on the effect that Prn deficiency has on infection and immunity to B. pertussis is crucial for the development of new strategies to control this disease. Here, we characterized the effect of Prn production by B. pertussis on human and murine dendritic cell (DC) maturation as well as in a murine model for pertussis infection. We incubated human monocyte-derived DCs (moDCs) with multiple isogenic Prn knockout (Prn-KO) and corresponding parental B. pertussis strains constructed either in laboratory reference strains with a Tohama I background or in a recently circulating clinical isolate. Results indicate that, compared to the parental strains, Prn-KO strains induced an increased production of pro-inflammatory cytokines by moDCs. This pro-inflammatory phenotype was also observed upon stimulation of murine bone marrow-derived DCs. Moreover, RNA sequencing analysis of lungs from mice infected with B. pertussis Prn-KO revealed increased expression of genes involved in cell death. These in vitro and in vivo findings indicate that B. pertussis strains which do not produce Prn induce a stronger pro-inflammatory response and increased cell death upon infection, suggesting immunomodulatory properties for Prn.